Сварочные материалы: состояние и тенденции развития - Походня, И.К. (Автоматическая сварка, 2003)
Представлены данные о современном производстве и потреблении стали в различных регионах мира. В связи с прогрессом в машиностроении, судостроении, строительстве и других отраслях потребуется снижение массы сварных конструкций, повышение их надежности и долговечности, снижение энергоемкости сварочных работ. Указанные задачи можно решить путем использования в ответственных конструкциях высокопрочных низколегированных (ВПНЛ) сталей. Приведены данные о состоянии металлургии и технологии сварки ВПНЛ сталей в России и Украине. Рассмотрены проблемы сварки ВПНЛ сталей и тенденции их развития, сформулированы направления дальнейших исследований. Рассмотрено состояние разработки сварочных материалов общего назначения, даны рекомендации по их совершенствованию. Data are presented about today production and consumption of steel in different regions of the world. The progress in machine-building, shipbuilding, civil engineering and other branches will require the reduction in mass of welded structures, increase in their reliability and life, reduction in energy consumption in welding operations. The above-mentioned problems can be solved by using high-strength low-alloy (HSLA) steels in critical structures. Data are given about the state-of-the-art of metallurgy and technology of HSLA welding in Russia and Ukraine. The problems of welding HSLA steels and tendencies of their development are considered and trends for their further investigation are formulated. State-of-the-art of development of general-purpose welding consumables is described and recommendations for their improvement are given.